Implementasi Model Pembelajaran Cooperative Integrated Reading and Composition (CIRC) dalam Meningkatkan Kemampuan Berpikir Kritis Siswa (Studi Kasus di MINU Bojonegoro) - Afida, Febrian Nafisa Nurul (Madrasah Ibtidaiyah Education Journal, 2025)
Education has an important role in forming superior quality human resources, especially in facing the challenges of the 21st century, which demand critical, collaborative, and creative thinking skills. This research aims to explore the implementation of the Cooperative Integrated Reading and Composition (CIRC) learning model in improving students' critical thinking skills at MINU Bojonegoro. The method used was Classroom Action Research (PTK) with research subjects of 28 grade 5 students. The research was carried out in two cycles, each consisting of three meetings. The research results show that the application of the CIRC model significantly improves students' reading, writing, and critical thinking skills. Through group discussions and writing responses to readings, students learn to analyze information, evaluate arguments, and organize thoughts systematically. Although there are challenges in implementing this model, the teacher's role as a facilitator is very important to create an inclusive learning environment. These findings indicate that the CIRC model can be an effective solution in improving students' critical thinking skills in elementary schools, as well as making a positive contribution to learning innovation at MINU Bojonegoro.